Pengaruh Klasifikasi Ilmu Terhadap Kurikulum Pendidikan Agama Islam Dalam Perspektif Ulama - Mahyudin Ritonga (EDUKASI : Jurnal Pendidikan Islam (e-Journal), 2017)
This paper describes a problem that is related to science in the field of scholars and its influence on the curriculum of Islamic education. The approach used in this paper is methodical, where the data sought in accordance with the context of the problem, while the analysis used is. This paper is al-Farabi which provides the science of discipleship on the basis of fundamental ontology, truth of evidence, and benefits. Al-Ghazali gives value in terms of matter and terms. Ibn Khaldun gave the science of naqliyyah and 'aqliyyah. The influence of science in Islamic education curriculum since the time of development of Islam until now. The thought of al-Farabi had a major influence on the curriculum of Islamic Education in the early period of Islamic history. Al-Ghazali through the period of influence since the period of the Seljuk Bans to the present day. While the science of science by Ibn Khaldun looks its influence is preserved madrasah. The idea of al-Attas looks its influence on the theory of Islamization of contemporary science and the development of Islamic educational institutions.